2014
DOI: 10.1021/nn501031t
|View full text |Cite
|
Sign up to set email alerts
|

Near- and Far-Field Properties of Plasmonic Oligomers under Radially and Azimuthally Polarized Light Excitation

Abstract: We present a comprehensive experimental and theoretical study on the near- and far-field properties of plasmonic oligomers using radially and azimuthally polarized excitation. These unconventional polarization states are perfectly matched to the high spatial symmetry of the oligomers and thus allow for the excitation of some of the highly symmetric eigenmodes of the structures, which cannot be excited by linearly polarized light. In particular, we study hexamer and heptamer structures and strikingly find very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…The particular amplitude modulation patterns analyzed here are potentially representative of a class of quasi-one-dimensional multipolar modes, and related systems such as modes in kinked wires [25], asymmetric rods [72], and higher-order modes of nanoparticle and nanohole edges [73,74] are suitable candidates for similar hybridization effects. This work also informs further development and evaluation of SPR sensors and devices derived from metal nanorods using other excitations such as shaped near-field excitation [75] or unconventional polarization [76]. Efforts to couple quantum dots [77,78] or absorptive layers [79] in the near field of nanorods will benefit from consideration of local field enhancement at antinodes as a function of location on the nanorod.…”
Section: Discussionmentioning
confidence: 91%
“…The particular amplitude modulation patterns analyzed here are potentially representative of a class of quasi-one-dimensional multipolar modes, and related systems such as modes in kinked wires [25], asymmetric rods [72], and higher-order modes of nanoparticle and nanohole edges [73,74] are suitable candidates for similar hybridization effects. This work also informs further development and evaluation of SPR sensors and devices derived from metal nanorods using other excitations such as shaped near-field excitation [75] or unconventional polarization [76]. Efforts to couple quantum dots [77,78] or absorptive layers [79] in the near field of nanorods will benefit from consideration of local field enhancement at antinodes as a function of location on the nanorod.…”
Section: Discussionmentioning
confidence: 91%
“…In related studies, even the excitation of a single atom or ion in free space with radially polarized photons was proposed for greatly enhancing the coupling efficiency . All these and many other studies show how advantageous and versatile such polarization‐tailored light beams are for the all‐optical study of nanoscopic systems. Also recent theoretical studies underline these capabilities of such tailored fields .…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons in our research we choose a seven particle cluster as oligomer, because it can provide data which can be compared not only with plasmonic (see ref. []) but also all‐dielectric oligomer designs (see refs. []).…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, several solutions were proposed. Namely, it has been demonstrated that the control of excitation polarization can modify the near‐field and the far‐field response of plasmonic oligomer . Another approach for active control of hot spots in plasmonic oligomers proposed recently involves changing the excitation geometry to the opposite one.…”
Section: Introductionmentioning
confidence: 99%